KEMAMPUAN BERPIKIR KREATIF MAHASISWA DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN MATEMATIKA SAAT PANDEMI COVID-19 - Novi Nurhayati; Rustanto Rahardi (IKIP Siliwangi, 2021)
This study aims to describe students' creative thinking skills in developing mathematics learning media. The research method used is descriptive qualitative method. The subjects of this study were 27 students majoring in mathematics education at a state university in Malang. The collection technique is a project-based group assignment in developing instructional media and the analysis technique uses the indicators used by following the indicators of creative thinking skills and data collection is the assessment of product results and interviews if needed. The results of the study show that the capability to think actively of students in developing learning media is included in the creative model of modification, namely changing the shape of a product so that it becomes more attractive and more practical (2) students develop mathematics learning media based on the problems found, in order to assist students in understanding the learning material; (3) the level of student creativity in developing learning media is very high despite the covid-19 pandemic.